Impact of Depression on Patients With Idiopathic Pulmonary Fibrosis - Tzouvelekis, Argyris; Karampitsakos, Theodoros; Kourtidou, Sofia; Bouros, Evangelos; Tzilas, Vasilios; Katsaras, Matthaios; Antonou, Chrysoula; Dassiou, Maria; Bouros, Demosthenes (Frontiers in Medicine, 2020)
Introduction: Depression is prevalent in patients with Idiopathic Pulmonary Fibrosis (IPF). The impact of depression on quality of life and its correlation with disease severity in patients with IPF has not been thoroughly evaluated on prospective studies. Patients and Methods: Between 2016 and 2017, we prospectively enrolled 101 patients (80 male, mean age (years) +SD: 70.8+8.1) with IPF (mean GAP score+SD: 4.7+1.8) without previous diagnosis of depression. Depressive symptoms were evaluated with Beck's depression inventory-II (BDI-II). Disease severity was evaluated with pulmonary function (FVC, DLCO) and exercise capacity measures. Symptom burden was assessed by cough and dyspnea scales. Health Related Quality of Life (HRQL) was assessed with two questionnaires. Results: Data for analysis was available from 98 patients (97%). Forty two patients (42.9%) presented with depressive symptoms scoring≥14. A significant association between depressive symptoms and measures of: 1) disease severity: a) GAP score: r=0.32, p=0.007, b) DLCO: r=-0.28, p=0.007, c) 6MWD: r=-0.39, p=0.017, 2) symptom burden: a) cough: r=-0.57, p<0.001, b) dyspnea (Borg: r=0.54, p<0.001, mMRC: r=0.55, p<0.001, SOBQ: r=0.57, p<0.001 and 3) HRQL: a) SGRQ: (Total score: r=0.68,p<0.001, Activity Score: r=0.60, p<0.001, Impact score: r=0.68, p<0.001, Symptoms score: r=0.60, p<0.001, b) K-BILD: r=-0.66, p<0.001), was identified. There was no statistically significant difference in BDI-II (p=0.62) and SGRQ (p=0.64) one year after treatment with antifibrotics. Conclusions: Patients with IPF and severe functional impairment tend to have increased risk for depression development and poor quality of life. Further prospective studies should investigate the role of antidepressant drug therapy in patients with IPF and comorbid depression.